A Survey of Avian Influenza in Tree Sparrows in China in 2011 - Han, Yan; Hou, Guangyu; Jiang, Wenming; Han, Chunhua; Liu, Shuo; Chen, Jie; Li, Jinping; Zhang, Peng; Huang, Baoxu; Liu, Yuehuan; Chen, Jiming (PLOS ONE, 2012)
Tree sparrows (Passer montanus) are widely distributed in all seasons in many countries. In this study, a survey and relevant experiments on avian influenza (AI) in tree sparrows were conducted. The results suggested that the receptor for avian influenza viruses (AIVs), SAα2,3Gal, is abundant in the respiratory tract of tree sparrows, and most of the tree sparrows infected experimentally with two H5 subtype highly pathogenic avian influenza (HPAI) viruses died within five days after inoculation. Furthermore, no AIVs were isolated from the rectum eluate of 1300 tree sparrows, but 94 serological positives of AI were found in 800 tree sparrows. The serological positives were more prevalent for H5 subtype HPAI (94/800) than for H7 subtype AI (0/800), more prevalent for clade 2.3.2.1 H5 subtype HPAI (89/800) than for clade 2.3.4 (1/800) and clade 7.2 (4/800) H5 subtype HPAI, more prevalent for clade 2.3.2.1 H5 subtype HPAI in a city in southern China (82/800) than in a city in northern China (8/800). The serological data are all consistent with the distribution of the subtypes or clades of AI in poultry in China. Previously, sparrows or other passerine birds were often found to be pathogenically negative for AIVs, except when an AIV was circulating in the local poultry, or the tested passerine birds were from a region near waterfowl-rich bodies of water. Taken together, the data suggest that tree sparrows are susceptible to infection of AIVs, and surveys targeting sparrows can provide good serological data about the circulation of AIVs in relevant regions.